What did you eat yesterday? 17 - Yoshinaga, Fumi, 1971- (Vertical, 2021)
"Shiro and Kenji are now well past their youthful years, and with a stable relationship and a stable career for them both, what could possibly go wrong? But Kenji finds himself in a bind one evening after a few drinks with one of his hair salon regulars. Meanwhile, a mysterious and beautiful woman greets Shiro with a friendly smile on the street during their grocery shopping, and Shiro insists that he doesn't know her"--